IL-1ra anti-inflammatory cytokine polymorphism is associated with risk of gastric cancer and chronic gastritis in a Brazilian population, but the TNF-beta pro-inflammatory cytokine is not - Garcia Oliveira, J. [UNESP]; Cristina Duarte, M. [UNESP]; Elizabete Silva, A. [UNESP] (Springer, 2012)
Genetic polymorphisms in genes that codify inflammatory cytokines have been associated with gastric carcinogenesis. This study evaluated polymorphisms IL-1RN VNTR and TNFB+252A/G in a population from Southeast Brazil with regard to the risk of chronic gastritis and gastric cancer and the presence of an association of gastric lesions with risk factors such as gender, age, smoking, drinking and Helicobacter pylori infection. In this case-control study, polymorphism at IL-1RN VNTR was investigated using the allele-specific polymerase chain reaction method, while the polymerase chain reaction-restriction fragment length polymorphism technique was used to identify the TNFB+252A/G genotype in 675 Brazilian individuals [229 with chronic gastritis (CG), 200 with gastric cancer (GC) and 246 healthy individuals as controls (C)]. Multiple logistic regression analysis (log-additive, dominant, and recessive models) have not showed association of the genotype frequencies for the SNP TNFB+252A/G with risk of CG or GC. However, as for IL-1RN VNTR it was observed significant differences in all three analysis models, with higher values of OR in recessive model, both in the GC group (OR = 3.04, 95% CI = 1.41-6.56, p < 0.01) and CG (OR = 2.32, 95% CI = 1.10-4.90, p = 0.02) compared to the C group. In addition, the multiple logistic regression showed also an association with risk factors such as male gender, older age and alcohol intake regarded GC group. So, our results indicated that the IL-1RN*2 allele may increase the risk of gastric cancer and precancerous lesions in the Southeast Brazilian population, reinforcing the importance of host genetic factors in the susceptibility to gastric cancer and the participation of cytokines in both the inflammation and the carcinogenic process.
Keywords: Genetic polymorphism; Inflammation; IL-1RN; TNF-beta; Gastric carcinogenesis